Post-Translational Modifications of the Werner Syndrome Protein WRN - Machwe, Amrita; Orren, David K (Cytogenetic and genome research, 2025)
Werner syndrome has been an excellent model for the study of human aging and how chromosomal instability is related to phenotypes of normal aging including cancer. George Martin devoted his life to the study of Werner syndrome and human aging, and this review is dedicated to his memory. In this review, we highlight the post-translational modifications of WRN, the protein whose function is lacking in individuals with Werner syndrome. WRN is subject to phosphorylation, acetylation, ubiquitination, and SUMOylation. These modifications of WRN control its localization and function in the response to replication fork stress and repair of double-strand breaks that are a consequence of this stress.